Training in Tracker Software for Experimental Physics Education at SMA Plus Bahrul Ulum - Fitri Afriani; Devita Harijayanti; Apriliyani Harahap; Tri Kusmita; Rizka Utami; Yuant Tiandho (Indonesian Journal of Community Empowerment (IJCE), 2026)
Practical activities are an important component in physics learning because they help students understand concepts concretely through experiments and data analysis. This community service activity aims to improve the quality of physics learning by training students to use Tracker software as a video analysis-based practical media at SMA Plus Bahrul Ulum Sungailiat. The implementation method includes preparation, preparation of materials and guides, training, and evaluation. The material focused on mechanics concepts, namely free fall, parabolic motion, and simple pendulum motion. The training was conducted through the delivery of materials, discussion, and direct practice of video analysis using smartphones. The results showed an increase in teacher and student understanding and skills in technology-based practicals. The use of Tracker enables more efficient and accurate quantitative analysis, increases student engagement, and supports more active, meaningful STEM-based learning.